PROCESSING TECHNIQUES OF REMOVING ANTINUTRIENTS FROM OILSEED CAKES AS BY-PRODUCTS INTENDED FOR ANIMAL FEEDING - Vujetić, Jelena; Spasevski, Nedeljka; Dragojlović, Danka (Food and Feed Research, 2024)
Contemporary animal feed production increasingly embraces zero-waste strategies, focusing on the use of food waste and cost-effective by-products to promote environmental sustainability. Oilseed cakes, by-products from oil extraction, have emerged as valuable resources due to their nutritional benefits and diverse applications. However, their use in animal feed is challenged by various antinutritional factors (ANFs) such as glucosinolates, cyanogenic glycosides, phytic acid, saponins, sinapine, tannins, and enzyme inhibitors, which can negatively impact nutrient absorption, digestibility, and feed palatability. The chemical properties of these ANFs differ considerably, and their concentrations vary significantly depending on the plant type. This variability makes it difficult to pinpoint a universally effective method for their reduction and removal. This paper aims to provide an overview of the different ANFs present in oilseeds used for animal feed, their concentrations, and their adverse effects on animal health and feed intake. It also reviews traditional methods for ANF removal, including heating, autoclaving, soaking, and chemical treatments, and explores novel techniques such as fermentation and enzymatic methods based on previous studies.
Keywords: antinutrients; oilseed cake; food and feed diet; proteins